The Effect of Tennis on Physical Fitness Parameters and AttentionGathering Skills in Children Aged 7-8 Years: A Cross-Sectional Study - VATANSEVER , Ahmet; ÇOLAK , Serap; BAYAZIT , Betül (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2023)
This study aimed to examine the relationship between physical fitness and attention in tennis-playing children aged 7 to 8 years. 30 athletes registered with the tennis branch of ALKEV Sports Schools who regularly attended training sessions were compared to 30 sedentary students registered with ALKEV Private Schools (Mean age: 7.50 0.504 years, Mean height: 128.48 5.140 cm, Mean weight: 26.60 4.574 kg). On the children, physical fitness parameters including height, body mass, agility test, flamingo balance test, standing long jump, and 20-meter sprint test were administered. The children's attention levels were determined using the Bourdon Attention Test. Using the SPSS 25.0 software, the statistical analysis of the study's data was performed. Statistically significant differences in favor of the athletes were found in the 20-meter sprint, vertical jump, flamingo balance, agility and Bourdon Attention Test (p 0.05) parameters.